Efficacy and safety of abobotulinumtoxinA liquid formulation in cervical dystonia: A randomized‐controlled trial. Issue 11 (21st September 2016) - Poewe, Werner; Burbaud, Pierre; Castelnovo, Giovanni; Jost, Wolfgang H.; Ceballos‐Baumann, Andres O.; Banach, Marta; Potulska‐Chromik, Anna; Ferreira, Joaquim J.; Bihari, Katalin; Ehler, Edvard; Bares, Martin; Dzyak, Lyudmyla A.; et al.
ABSTRACT: Background: Approved botulinum toxin A products require reconstitution. AbobotulinumtoxinA solution for injection is a ready‐to‐use liquid formulation of abobotulinumtoxinA. Objectives: The objective of this study was to demonstrate the superior efficacy of abobotulinumtoxinA solution for injection to placebo and to test the noninferior efficacy of abobotulinumtoxinA solution for injection versus abobotulinumtoxinA (dry formulation) in cervical dystonia. Methods: This was a phase‐3, multicenter, prospective, double‐blind, randomized, active, and placebo‐controlled study (N = 369). Patients with cervical dystonia were randomized (3:3:1) to abobotulinumtoxinA solution for injection 500 U, abobotulinumtoxinA 500 U, or placebo. Following the double‐blind phase, patients received abobotulinumtoxinA solution for injection, open‐label, for up to 4 cycles. The primary outcome was change from baseline at week 4 of the Toronto Western Spasmodic Torticollis Rating Scale total score. Secondary measures included change from baseline or cycle baseline in Toronto Western Spasmodic Torticollis Rating Scale scores. Results: At week 4, both products were superior to placebo (Toronto Western Spasmodic Torticollis Rating Scale total score least square mean decrease from baseline, abobotulinumtoxinA solution for injection 500 U −12.5, abobotulinumtoxinA 500 U −14.0, placebo −3.9; P < .0001 vs placebo). The noninferiority limit of 3 points in the Toronto Western Spasmodic Torticollis Rating Scale total score at week 4 was not met for abobotulinumtoxinA solution for injection versus abobotulinumtoxinA. Toronto Western Spasmodic Torticollis Rating Scale total score reductions were maintained for up to 4 cycles of abobotulinumtoxinA solution for injection open‐label follow‐up treatment. Safety profiles of abobotulinumtoxinA solution for injection and abobotulinumtoxinA were similar, with dysphagia and injection‐site pain the most frequent drug‐related adverse events. Conclusions: Although the predefined noninferiority criterion was not met, abobotulinumtoxinA solution for injection was similarly effective to freeze‐dried abobotulinumtoxinA in reducing Toronto Western Spasmodic Torticollis Rating Scale total scores with a similar safety profile. AbobotulinumtoxinA solution for injection efficacy was maintained with chronic open‐label treatment, and this novel formulation may add convenience as well as dosing accuracy to treatment with abobotulinumtoxinA. © 2016 International Parkinson and Movement Disorder Society